2002
DOI: 10.1046/j.1471-4159.2002.01115.x
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine activation of adenosine A1 receptors blocks D1A but not D1B dopamine receptor desensitization

Abstract: Adenosine is known to modulate dopamine responses in several brain areas. Here, we show that tonic activation of adenosine receptors is able to impede desensitization of D 1 dopamine receptors. As measured by cAMP accumulation in transfected COS-7 cells, long-term exposure to dopamine agonists promoted desensitization of D 1B receptor but not that of D 1A receptor. The inability of D 1A receptor to desensitize was a result of the adenosine present in culture medium acting through activation of adenosine A1 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Within the striatum, the D 5 receptor is expressed predominantly in cholinergic interneurons, whereas D 1 receptors predominate in GABAergic neurons (Rivera et al, 2002;Centonze et al, 2003). Unlike the D 1 receptor, D 5 receptors do not form functional complexes with A 1 adenosine receptors (Le Crom et al, 2002), and plasma membrane localization of the D 5 (but not the D 1 ) receptor requires N-glycosylation (Karpa et al, 1999). These observations indicate significant structural differences between the receptor subtypes, and this is consistent with the recent observation of differential physicochemical susceptibility of G s -coupled versus G q -coupled D 1 -like sites to reducing agents or plasma membrane perturbations (Panchalingam and Undie, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Within the striatum, the D 5 receptor is expressed predominantly in cholinergic interneurons, whereas D 1 receptors predominate in GABAergic neurons (Rivera et al, 2002;Centonze et al, 2003). Unlike the D 1 receptor, D 5 receptors do not form functional complexes with A 1 adenosine receptors (Le Crom et al, 2002), and plasma membrane localization of the D 5 (but not the D 1 ) receptor requires N-glycosylation (Karpa et al, 1999). These observations indicate significant structural differences between the receptor subtypes, and this is consistent with the recent observation of differential physicochemical susceptibility of G s -coupled versus G q -coupled D 1 -like sites to reducing agents or plasma membrane perturbations (Panchalingam and Undie, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that D1R and D5R expressed in same heterologous expression systems can both undergo agonist‐induced desensitization (Jarvie et al . 1993; Le Crom et al . 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, A 1 R and D 1 R have been shown to physically interact in the central nervous system with the formation of a heteromeric complex that leads to the uncoupling of the D 1 R from its Gs-like protein complex (178,188). However, in COS-7 cells and fibroblasts heterologously expressing A 1 R, D 1 R, and D 5 R, activation of A 1 R blocks the desensitization of D 1 R but not D 5 R (348), another instance of cell specific effect or related to gene overexpression.…”
Section: Dopamine Receptor Interactionsmentioning
confidence: 99%